2020
DOI: 10.5435/jaaosglobal-d-20-00031
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Orthopaedic Injuries in the Prison Population

Abstract: Under the landmark 1976 Estelle v. Gamble decision, the U.S. Supreme Court affirmed that prisoners have a constitutional right to adequate medical attention and concluded that the Eighth Amendment is violated when corrections officials display "deliberate indifference" to an inmate's medical needs. 1 The manner in which states manage prison health care services that meet these legal requirements affects not only inmates' health, but also the public's health and safety and taxpayers' total corrections bill. Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Fifteen studies were from the United States, and 12 had IRB approval. Notably, 3 studies were exempted from IRB review (waived consent), 15 17 and 2 studies did not report their IRB status 18 , 19 (Supplemental Table 1, http://links.lww.com/AOSO/A345 ). Among the 12 studies with IRB approval, 6 included a waiver of consent, 13 , 20 24 while 6 did not report the status of consent waivers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen studies were from the United States, and 12 had IRB approval. Notably, 3 studies were exempted from IRB review (waived consent), 15 17 and 2 studies did not report their IRB status 18 , 19 (Supplemental Table 1, http://links.lww.com/AOSO/A345 ). Among the 12 studies with IRB approval, 6 included a waiver of consent, 13 , 20 24 while 6 did not report the status of consent waivers.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 12 studies with IRB approval, 6 included a waiver of consent, 13 , 20 24 while 6 did not report the status of consent waivers. 25 30 Four studies identified incarcerated patients through International Classification of Diseases (ICD) codes: Y92:14 X (prion as location of injury) or E849.7 (injury occurring in residential institution), 17 , 18 , 21 , 23 4 used admission or discharge locations, 16 , 23 , 27 , 28 8 used prison referral or electronic medical record review, 13 , 19 , 22 , 24 26 , 29 , 30 1 used prison billing data, 15 and 1 used prospective identification during consultation. 20 Using the ROBINS-E tool risk of bias assessment, 70.6% of the studies had high or very high concerns for bias (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Barreto Rocha et al found no studies addressing the epidemiology of traumatic orthopaedic injuries and their complications among prison populations 10 . However, developing knowledge of cultural considerations when working with someone who has been incarcerated may be important to those working in orthopaedic care because the reported incidence of violent and accident-based orthopaedic injuries is higher in the inmate population compared with the free world 11,12 .…”
Section: Cultural Considerationsmentioning
confidence: 99%